An Analysis of Thai Student Teacher Appropriate Internet Use Behaviour - Punnee Leekitchwatana; Paitoon Pimdee (My University, 2021)
The goals of this research were to analyse and develop a Hierarchical Linear Model (HLM) of appropriate Internet use behaviour of Thai student teachers. The sample group consisted of 1,800 student teachers studying for their bachelor’s degree at 30 Thai government educational institutions. The research tool used was a questionnaire with content validity and reliability at 0.83 – 0.92. Mean (¯(x )), standard deviation (S.D.), and HLM were used to analyse the data. The findings revealed that appropriate Internet use behaviour in Thai student teachers was at a high level. Additionally, the HLM for appropriate Internet use behaviour for Thai student teachers consisted of two levels of predictor variables. The first level was the student teacher level, in which six of the hypothesized nine predictor variables had statistical significance. Five had a positive effect, which included ability, affect, family situation, gender, and GPA, while one variable had a negative effect, which was income. The second level was the institutional level, which contained two predictor variables with statistical significance, friends and educational institution situation, with both having positive effects. Friends had a direct effect on behaviour at the educational institution level, while educational institution situation had an effect through ability.
Keywords: Bachelor; Variables; Sample (material); Institution; Educational institution; Validity; Bachelor degree; Impact of Technology on Adolescents